The Doctrinal Unfoldment of Marine Pollution Wrongdoing: On the activation of environmental pollution crime - Yiyang HAO (Haiyang Kaifa yu guanli, 2023)
The application of environmental pollution crime in judicial practice in China is not flexible enough, so it is necessary to study it from the angle of criminal law hermeneutics. Compared with the theory of legislation, the theory of interpretation is a more appropriate path. Doctrinal analysis of marine pollution wrongdoing is conducive to activating the crime of environmental pollution. We should adopt the theory of ecological human-centered legal interests to define the protection interests of environmental pollution crime. Taking the act of polluting the sea as an example, guided by the interests of the law of protection, the "three-step approach" limits the scope of the "ocean" protected by the crime of polluting the environment to the sea area directly or indirectly affecting human life after pollution. From the perspective of functionalism, marine pollution can be divided into three types: intentional disposal, operational violation and accident, and each type of criminal behavior applies different treatment modes. The crime of polluting the environment and the crime of releasing dangerous substances, the crime of endangering public security by dangerous methods and the corresponding crime of negligence, the crime of illegal manufacturing, transportation and storage of dangerous substances and the crime of major liability accidents, there is a cross and competition relationship, should be fully evaluated according to the relevant judicial interpretation and other provisions, without violating the principle of repeated evaluation. In the case of marine pollution caused by ship collision, the liability of collision accident and pollution accident should be distinguished, and the criminal liability of each subject should be evaluated comprehensively.